Systemic Hypertension as a Risk Factor for Primary Open-Angle Glaucoma in Adults - Muhammad Rizwan, Rai Muhammad Azam, Muhammad Sarfraz, Abdul Ghafoor, Ahmad Ejaz, Hafiz Muhammad Mudassar Javed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Primary open-angle glaucoma (POAG) is a leading cause of irreversible blindness worldwide. While elevated intraocular pressure is a known risk factor, vascular components such as systemic hypertension have also been implicated in its pathogenesis. Objective: To determine the association between systemic hypertension and primary open-angle glaucoma in adults. Methods: This case-control analytical study was conducted at Sahiwal Teaching Hospital, Sahiwal from February 2023 to July 2023. A total of 325 participants were included, comprising 162 cases (patients with POAG) and 163 controls (individuals without POAG), matched for age and gender. Demographic and clinical data were obtained using a structured questionnaire. This included information on age, gender, duration of hypertension, medication use, and lifestyle factors. Blood pressure was measured using a calibrated mercury sphygmomanometer in a sitting position after a five-minute rest. Results: Systemic hypertension was present in 66.7% of patients with POAG compared to 45.4% of controls (p < 0.001). The unadjusted odds ratio for POAG in hypertensive individuals was 2.43 (95% CI: 1.57–3.78, p < 0.001). After adjusting for age, gender, and smoking status, systemic hypertension remained independently associated with POAG (adjusted OR = 2.18, 95% CI: 1.35–3.52, p = 0.002). Additionally, a longer duration of hypertension (>10 years) and the use of multiple antihypertensive medications were more frequent among POAG patients (p = 0.03 and p = 0.02, respectively). Conclusion: It is concluded that systemic hypertension is significantly associated with primary open-angle glaucoma in adults. Prolonged duration and severity of hypertension further increases the risk. These findings emphasize the need for integrated cardiovascular and ophthalmologic screening in hypertensive individuals to enable early detection and prevention of glaucomatous vision loss. Keywords: POAG, Patients, Retinal, Cells, Chronic, Neuropathy